Synthesis of h- and α -MoO3 by refluxing and calcination combination: Phase and morphology transformation, photocatalysis, and photosensitization - Pannipa Wongkrua (2018)
Hexagonal molybdenum oxide (h-MoO3) nano- and microrods were successfully synthesized by refluxing of (NH4)6Mo7O24·4H2O solutions with the pH 1 at 90°C for 1, 3, 5, and 7 h and were further transformed into orthorhombic molybdenum oxide (α-MoO3) microplates by calcination at 450°C for 6 h. These selected products were used to determine the degradation of methylene blue dye under 35 W xenon lamp for 0-180 min, due to the photocatalysis and photosensitization processes. In this research, catalytic activity of the metastable h-MoO3has higher efficiency than that of the thermodynamically stable α-MoO3. Their phase and morphology transformation was also explained according to the experimental results. © 2013 Pannipa Wongkrua et al.